Peran Komunitas Dalam Mengembangkan Budaya Dan Kearifan Lokal Di Era Media Digital - II, Harianto; Amin, Teguh Satria; Zulfitri, Zulfitri (ANTHOR: Education and Learning Journal, 2022)
Communities have an important role in preserving culture and also local wisdom in the area where they live and live. The role of the community is very important to maintain and also develop local culture and wisdom and traditions so that they continue to live and accompany the community in every life. This research aims to determine the role of society in the development of culture and local wisdom in the era of digital media and globalization. The research was conducted using a qualitative descriptive method that collects data in an incentive and systematic way to obtain information and also knowledge about the role of the community in developing local culture and wisdom in the digital media era. In this studyresearchers will interact and communicate with the community, especially in the province ofNorth Sumatra regarding the role of the community in developing local culture and wisdom in the digital media era. In particular, this era of globalization has had a huge influence onthe world of art and culture, especially the local cultures of the local community, which are beginning to erode and are also in danger of extinction.